Role of GluA3 AMPA Receptor Subunits in the Presynaptic and Postsynaptic Maturation of Synaptic Transmission and Plasticity of Endbulb−Bushy Cell Synapses in the Cochlear Nucleus - Antunes, Flora M. (J Neurosci, 2020)
The AMPA receptor (AMPAR) subunit GluA3 has been suggested to shape synaptic transmission and activity-dependent plasticity in endbulb-bushy cell synapses (endbulb synapses) in the anteroventral cochlear nucleus, yet the specific roles of GluA3 in the synaptic transmission at endbulb synapses remains unexplored. Here, we compared WT and GluA3 KO mice of both sexes and identified several important roles of GluA3 in the maturation of synaptic transmission and short-term plasticity in endbulb synapses. We show that GluA3 largely determines the ultrafast kinetics of endbulb synapses glutamatergic currents by promoting the insertion of postsynaptic AMPARs that contain fast desensitizing flop subunits. In addition, GluA3 is also required for the normal function, structure, and development of the presynaptic terminal which leads to altered short term-depression in GluA3 KO mice. The presence of GluA3 reduces and slows synaptic depression, which is achieved by lowering the probability of vesicle release, promoting efficient vesicle replenishment, and increasing the readily releasable pool of synaptic vesicles. Surprisingly, GluA3 also makes the speed of synaptic depression rate-invariant. We propose that the slower and rate-invariant speed of depression allows an initial response window that still contains presynaptic firing rate information before the synapse is depressed. Because this response window is rate-invariant, GluA3 extends the range of presynaptic firing rates over which rate information in bushy cells can be preserved. This novel role of GluA3 may be important to allowing the postsynaptic targets of spherical bushy cells in mice use rate information for encoding sound intensity and sound localization. SIGNIFICANCE STATEMENT We report novel roles of the glutamate receptor subunit GluA3 in synaptic transmission in synapses between auditory nerve fibers and spherical bushy cells (BCs) in the cochlear nucleus. We show that GluA3 contributes to the generation of ultrafast glutamatergic currents at these synapses, which is important to preserve temporal information about the sound. Furthermore, we demonstrate that GluA3 contributes to the normal function and development of the presynaptic terminal, whose properties shape short-term plasticity. GluA3 slows and attenuates synaptic depression, and makes it less dependent on the presynaptic firing rates. This may help BCs to transfer information about the high rates of activity that occur at the synapse in vivo to postsynaptic targets that use rate information for sound localization.